Penerapan Model Grover dalam Memprediksi Kebangkrutan pada Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Putri, Berlian Ernita; Yantiana, Nella; Karpriana, Angga Permadi (Magister Manajemen Universitas Wisnuwardhana, 2024)
This study aims to observe and predict bankruptcy in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) using the Grover analysis method. The population size is 3 (three) years with the period (2021-2023). The data analysis method in this research is descriptive quantitative using secondary data sources. The data analysis techniques used are descriptive statistics and Accuracy Level Test. The results showed that the most accurate prediction model in predicting bankruptcy of pharmaceutical sector companies is Grover with an accuracy rate of 97% and an error rate of 3%. Judging from the 2021-2023 period, there are 13 companies listed as the pharmaceutical sector on the IDX. This shows that there are 11 companies that are in the category of not bankrupt or in a healthy condition with a G-Score value above 0.01. However, there are 2 companies that experience gray areas, namely PT Indofarma (Persero) Tbk which occurred in 2022 and 2023 and PT Kimia Farma (Persero) Tbk which occurred in 2023.